IMPLEMENTASI E-GOVERNMENT DALAM PEMBERIAN DAN PERPANJANGAN IZIN TINGGAL TERBATAS MELALUI KANTOR IMIGRASI - Kristi Wibowo, Pascalis Danny; Mastur, Anida Sri Rahayu (Polteknik Imigrasi, 2022)
Abstract (In English). The purpose of this article is to understand the implementation of e-government in granting and adding limited stay permits through the Immigration Office. The method used is a qualitative approach, data collection through literature study, and data analysis techniques used interactive models to draw conclusions. As a result, the implementation of e-government in the granting and addition of limited residence permits through the Immigration Office is a form of excellent service in the field of immigration. Excellent service supported by professionalism, accountability, synergy, transparency, and innovation through information management. Excellent service that provides assurance in time and convenience.